Mechanical Ventilator-Associated Pneumonia in the COVID-19 Pandemic Era: A Critical Challenge in the Intensive Care Units - Mircea Stoian; Adina Andone; Sergiu Rareș Bândilă; Danusia Onișor; Sergiu Ștefan Laszlo; Gabriela Lupu; Alina Danielescu; Dragoș-Florin Baba; Anca Meda Văsieșiu; Andrei Manea; Adina Stoian (Antibiotics)
Background/Objectives: Ventilator-associated pneumonia (VAP) is the most common nosocomial infection encountered in the intensive care unit (ICU) and is associated with prolonged hospitalization and increased mortality. We evaluated the causative pathogens involved and their resistance to the major classes of antibiotics in patients with VAP and assessed the differences between patients with and without coronavirus disease 2019 (COVID-19). Materials and Methods: This study was a single-center, cross-sectional, retrospective analysis involving 122 patients who were hospitalized in the ICU of Târgu Mureș County Clinical Hospital from 1 April 2021, to 1 April 2023. This study compares patients with VAP in COVID-19 and non-COVID-19 groups, examining the clinical progression, duration of ventilation and hospitalization, mortality, pathogen distribution, and the emergence of multidrug-resistant strains. Results: A length of stay in the ICU exceeding 11.5 days was associated with the development of multidrug-resistant (MDR) infections (AUC: 0.708, p < 0.001). Similarly, a duration of MV exceeding 196 h was associated with MDR acquisition (AUC: 0.695, p = 0.002). Additionally, a Clinical Pulmonary Infection Score (CPIS) greater than 5 was associated with MDR development (AUC: 0.854, p < 0.001) in the whole group of patients. The most commonly isolated strains were Acinetobacter spp., Pseudomonas spp., Klebsiella spp., and Staphylococcus aureus. Among non-COVID-19 patients, there was a notably higher frequency of MDR Acinetobacter baumannii. A bacterial resistance to carbapenems was found in Acinetobacter spp. (51.6%), Klebsiella spp. (22.6%), and Pseudomonas spp. (25.8%). Conclusions: COVID-19 patients experienced longer ventilation, higher mortality, and an increased risk of developing MDR. Carbapenem resistance was universal in Acinetobacter spp. and Klebsiella pneumoniae, whereas resistance in Pseudomonas aeruginosa was more prevalent among non-COVID-19 patients. The Clinical Pulmonary Infection Score (CPIS) strongly correlates with developing MDR pathogens in both patient groups.